Study of the severity of stroke at the time of presentation in diabetic patients correlating with glycemic control - Patibandla, Sivaji; Appikatla, Tumbanatham; K., Jayasingh (International Journal of Advances in Medicine, 2017)
Background: Diabetes mellitus is a well-recognized risk factor for stroke. The NIHSS (National institute of health stroke scale) is a tool used objectively to quantify the impairment caused by a stroke. However, the effect of glycemic control regardless of the presence of DM on the clinical picture of stroke and its impact on the severity is not fully investigated. There are numerous studies on microvascular complications but there are only a few studies on strokes in diabetics. Therefore, this study was conducted to assess the impact of diabetes on the pattern and severity of stroke in our population. Methods: This is cross sectional observational study, carried at Mahatma Gandhi Medical College And Research Institute, Pondicherry, India from December 2014-15. Sixty patients who presented with features of stroke and satisfy inclusion criteria were enrolled in study. Stroke pattern was identified using CT scan and severity of stroke was assessed by NIHSS score. Statistical analysis was done by using chi-square test (p <0.005 = significant). Results: The mean age in patients was 61.683±12.97. The ratio of male to female was 2.1:1 showing male preponderance. With increase in HbA1c levels more number of cases were found to have severe stroke and it is statically significant (p = 0.0001) as per NIHSS score. Conclusions: In diabetic patients the severity of stroke is related to glycemic control. Higher the blood HbA1c level, more severe is the neurological impairment. Hence effective lowering of HbA1c level may reduce the occurrence of severe neurological impairment in diabetic patients. We suggest the need for routine monitoring of HbA1c level may be used as a measure for secondary prevention of stroke in diabetic patients.